Attained pregnancy among women with a prosthetic heart valve. (September 2019) - Siu, Samuel C.; Lam, Melody; Allen, Britney; Richard, Lucie; Shariff, Salimah Z.; Garg, Pallav; Silversides, Candice K.; Ray, Joel G.
Abstract: Background: Women with prosthetic heart valves are at higher risk for adverse outcomes during pregnancy. The rates of achieved pregnancy, regardless of the pregnancy outcome, are largely unknown in this group of women. Objective: To determine the rate of pregnancy in women with prior heart valve replacement, and compare that to women without known heart disease. Study Design: A retrospective matched population-based cohort study was done between April 1994 and March 2017, in Ontario, Canada, where universal health care is available. Administrative healthcare databases were used to identify study participants, exposures and outcomes. Each woman of child-bearing age who had a bioprosthetic or mechanical mitral or aortic valve replacement (valve replacement group) was matched to four women without heart disease (community comparison group) -- by age, year of cohort entry, any recent prior pregnancy, geographic area of residence and income level. Starting after the date of cohort entry (defined as the date valve replacement date in the valve replacement group), participants were assessed for a recognized pregnancy, namely, a livebirth, stillbirth, miscarriage or induced abortion. Hazard ratios (HR) and 95% confidence intervals (CI) were further adjusted for age, immigrant status and comorbid medical conditions. Results: 1596 women with a valve replacement were matched with 6378 women in the community comparison group. After a median (interquartile range, IQR) duration of follow-up of 3.1 (1.0–5.6) and 2.7 (1.0–6.0) years, respectively, 98 women in the valve replacement group achieved a recognized pregnancy (0.63 per 100 person-years), compared to 607 women in the community comparison group (0.88 per 100 person-years) – an adjusted HR of 0.72 (95% CI 0.57-0.89). Within the valve replacement group, those with a mechanical valve were less likely to achieve a recognized pregnancy than those with a bioprosthetic valve (adjusted HR 0.57, 95% CI 0.38-0.87). Conclusion: Women who undergo aortic or mitral valve replacement are less likely to achieve a pregnancy than matched counterparts without heart disease. This information, and the reasons for why this is so, can inform decisions about the timing of valve replacement and pregnancy planning.